Pengaruh Pola Asuh Orang Tua terhadap Perkembangan Kemandirian Anak Didik PAUD Nurul Husna Kosambi Tangerang - Suryani Suryani; Chientya Annisa Rahman Putrie (Neolectura, 2021)
Educational goals are intended to be achieved by an educational institution. This goal can be achieved if there is a role from students. However, at the early childhood education level, there are still many children who are not independent. For this reason, children's independence needs to be developed. One of the developments of children's independence can be increased through parenting. This research method is causal quantitative research – comparative. This research was conducted at PAUD Nurul Husna in the 2017/2018 academic year. The time of the research was carried out from April to July 2018. This type of research was ex post facto. The research population is parents or guardians of PAUD Nurul Husna students, totaling 60 people. The research sample is 30 students obtained through random sampling technique. Data collection uses test and non-test evaluation tools based on a psychological scale. Data analysis techniques are normality test, homogeneity test, linearity test, and hypothesis testing using the SPSS program. The results of the study indicate that there is an influence of parenting patterns on the development of independence of PAUD Nurul Husna students for the 2017/2018 academic year.